Kapitalisme dalam Kacamata Karl Marx Mengungkap Realitas di Balik Sistem Ekonomi - ma'ruf, amar (Maliki Interdisciplinary Journal, 2024)
This article examines Karl Marx's thoughts on capitalism, focusing on an in-depth analysis of Das Kapital and key concepts such as exploitation, alienation, surplus value, the dynamics of capital and labor, and capitalist crises. Using qualitative research methods with a literature review approach, the article critically analyzes Marx's works and related secondary sources to explore how capitalism functions and the internal contradictions involved. The findings show that capitalism operates through the exploitation of the working class by capital owners, with surplus value at the core of capital accumulation. The article also finds that capitalist crises, such as declining profit rates and overproduction, result from the system's internal contradictions. The study aims to provide a deeper understanding of the relevance of Marx's theory in the context of contemporary capitalism, while encouraging further discussion on solutions to the structural inequalities produced by capitalism.